Proteome changes in Thai indigenous chicken muscle during growth period - Teltathum T. (2014)
Proteomic profiling of the pectoralis muscle of Thai indigenous chickens during growth period was analyzed using two-dimensional gel electrophoresis (2-DE) and matrix assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF/MS). A total of 259, 161, 120 and 107 protein spots were found to be expressed in the chicken pectoralis muscles at 0, 3, 6 and 18 weeks of age, respectively. From these expressed proteins, five distinct protein spots were significantly associated with chicken age. These protein spots were characterized and showed homology with phosphoglycerate mutase 1 (PGAM1), apolipoprotein A1 (APOA1), triosephosphate isomerase 1 (TPI1), heat shock protein 25 kDa (HSP25) and fatty acid binding protein 3 (FABP3). These five protein spots were categorized as follows: (i) the expression levels of PGAM1 and TPI1 proteins were positively correlated with chicken aging (p<0.05), (ii) the expression levels of APOA1 and FABP3 proteins were negatively correlated with chicken aging (p<0.05) and (iii) the expression levels of the HSP25 protein were up- and down-regulated during growth period. Moreover, the mRNA expression levels of the FABP3 and HSP25 genes were significantly decreased in muscle during the growth period (p<0.05), whereas no significant changes of the PGAM1, TPI1 and APOA1 gene expression from the chicken muscle was observed. The identified proteins were classified as metabolic and stress proteins. This demonstrates a difference in energy metabolism and stress proteins between age groups and shows that proteomics is a useful tool to uncover the molecular basis of physiological differences in muscle during the growth period. © Ivyspring International Publisher.